2018
DOI: 10.1093/jas/sky355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of constant or intermittent high temperature on egg production, feed intake, and hypothalamic expression of antioxidant and pro-oxidant enzymes genes in laying ducks1

Abstract: Heat stress is a major environmental factor contributing to lower production of poultry. The objective of present study was to evaluate the influence of constant or intermittent high temperature on the production performance and redox status of plasma and hypothalamus in laying ducks. A total of 288 weight- and laying-matched laying ducks were randomly assigned to 1 of 4 treatments (each with 6 replicates of 12 birds): control, pair-fed, constant high temperature (24 h, 34 ± 1°C), and intermittent high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Similarly, Christopher et al [81] reported a 32.7% decrease in laying rate (82.9 versus 55.8%) in heatstressed laying hens compared with hens reared under optimal thermal conditions. Similar results have also been reported in ducks [82]. A study conducted by Attia et al [10] revealed that plasma hormones and the laying rate decreased in hens reared under heat stress when compared to the supplemented groups.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Christopher et al [81] reported a 32.7% decrease in laying rate (82.9 versus 55.8%) in heatstressed laying hens compared with hens reared under optimal thermal conditions. Similar results have also been reported in ducks [82]. A study conducted by Attia et al [10] revealed that plasma hormones and the laying rate decreased in hens reared under heat stress when compared to the supplemented groups.…”
Section: Discussionsupporting
confidence: 82%
“…It appears from the above studies that heat stress directly affects reproductive function in vertebrates. However, an alternate explanation for these previously observed reproductive effects is that heat stress can have negative impacts on egg production and reproductive performance through the effect on feed intake and physiological characteristics of laying hens [4,5]. Decreased feed intake is known to affect the endocrine system, leading to acid-base imbalances and organ dysfunction [6].…”
mentioning
confidence: 99%
“…Egg quality variables (shape index, yolk color score, albumen height, Haugh units, proportions of albumen, yolk and shell) were determined as described previously ( Chen et al., 2015 ; Luo et al., 2018 ).…”
Section: Methodsmentioning
confidence: 99%